Suggestions for standardization of halal tourism in hospitality industry - Pamukçu, Hüseyin; Sarıışık, Mehmet (Emerald, 2020)
PurposeThe purpose of this paper is to determine the expectations of hotel guests regarding the halal standards in the hotels where they stay. Besides, the determination of differences in demographic characteristics of the participants is among the objectives of the research. Thus, taking into consideration the halal standard expectations of the participants, the results that will support the applications of accommodation establishments have been attempted to be figured out.Design/methodology/approachQuantitative research methods were used in this research. Owing to the lack of a specific scale in the related literature, the questionnaire used in the study was created as a result of pilot tests conducted with the expressions mentioned in the theoretical studies. In a sense, this research provides a basis for the development of a scale that was not available in this area. Analysis methods were decided by considering the preconditions for parametric test techniques.FindingsIslamic lifestyle is specified as the most common reason for choosing halal concept hotels. Additionally, there are some other outstanding reasons like halal food, safer holiday etc. Watching TV during the holidays is the least important reason to spend time. It has been determined that the attitude toward halal tourism changes according to gender and women’s attitude toward tourism is more positive than men’s. In addition to this, it is found out that the attitude of halal tourism differs by age for males, while it differs by educational status for women. It is ensured that potential entrepreneurs can achieve significant economic gains by attracting investors’ attention to this market. Besides, the possibility of meeting the holiday needs of the masses with religious sensitivities within the country is revealed by halal tourism. The emergence of sufficient tourism facilities will show that this group will be respected and valued. Hence, this will also contribute positively to social tolerance.Research limitations/implicationsHalal tourism is an issue for almost all tourism (accommodation, eating, recreation, transportation) businesses. However, this dissertation focused on accommodation establishments and other tourism enterprises were excluded from the scope of the study.Practical implicationsIt is believed that this study is authentic in the way it offers a universal halal tourism model for the hospitality industry as well as the comprehensive literature review that it is built on. Thus, it is expected to have a significant impact on both practical and theoretical knowledge.Originality/valueThis study is unique in terms of increasing the satisfaction of the people demanding the halal concept accommodation establishments can apply halal tourism and offering a standardization proposal for that. It is thought that this research is original and that it is important for both the practice field and the theoretical field to provide a standardization which can be applied in accommodation establishments.
Keywords: Halal standardization; Halal; Hospitality management; Islamic marketing; Halal tourism; 11. Sustainability; 1. No poverty; 16. Peace & justice; 3. Good health